PUNGSU: GEOMANSI LANSKAP KOREA - Qodarian Pramukanto (http://arl.faperta.ipb.ac.id/, 2012)
Geomancy is form-recognized art of earth’s ki energy interaction with community culture. Ki and its existence in a place can be identified because its linked to geographical features of landscape. In Korea, this spatial perception and thought about geographical environment is the pungsu. Pungsu is geomancy that examines and determines the sites that favorable for town, village, house or tomb. There are two approaches are applied in pungsu, i.e. compass school and form school. The compass school is developed from the basic idea/theory, while form school developed from systematic structure theory. This paper explain and discuss both approaches.